2022
DOI: 10.3390/jcm11061660
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Myocarditis after COVID-19 mRNA Vaccination

Abstract: Background: Myocarditis, even in a severe and lethal form, may occur after COVID-19 mRNA (BNT162b2) vaccination. However, its pathway, morphomolecular characterization and treatment are still unknown. Methods: Routine hematochemical screening, ECG, Holter monitoring, 2D echocardiogram cardiac magnetic resonance (CMR) and invasive cardiac studies (cardiac catheterization, selective coronary angiography, left ventriculography and left ventricular endomyocardial biopsy) are reported from three patients (39F-pt1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Lymphocytic and eosinophilic infiltration were also observed in myocarditis after smallpox vaccination and a mechanism of immune-mediated myocarditis has been speculated [ 9 ]. In addition, Frustaci et al reported three cases of pathohistologically defined eosinophilic myocarditis after COVID19 vaccination, referring to the possibility of eosinophilic myocarditis (hypersensitivity myocarditis) as an allergic reaction and the possibility that immunosuppressive therapy including steroids may be effective [ 10 ]. Considering the response to steroid pulse therapy, it is possible that this mechanism of eosinophil-mediated immunological injury to cardiomyocytes is also involved in this case.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytic and eosinophilic infiltration were also observed in myocarditis after smallpox vaccination and a mechanism of immune-mediated myocarditis has been speculated [ 9 ]. In addition, Frustaci et al reported three cases of pathohistologically defined eosinophilic myocarditis after COVID19 vaccination, referring to the possibility of eosinophilic myocarditis (hypersensitivity myocarditis) as an allergic reaction and the possibility that immunosuppressive therapy including steroids may be effective [ 10 ]. Considering the response to steroid pulse therapy, it is possible that this mechanism of eosinophil-mediated immunological injury to cardiomyocytes is also involved in this case.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 468 patients with suspected myocarditis and cardiac MRI findings were included in this study ( n = 294 from case reports/case series with IPD 5,7,9,11–66,68,70–73,75–87,89,91–95,97–107 and n = 174 from five case series 67,69,74,88,90 with AD). Based on data provided by 100 out of 102 studies, all included patients met CDC criteria for suspected myocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…Timely diagnosis and management are crucial for improving the prognosis of this complication 5 . An increasing number of studies have utilized cardiac MRI, as the most important noninvasive diagnostic tool, to assess suspected myocarditis associated with COVID‐19 vaccination 5–105 . One narrative review article attempted to address the pattern of myocardial injury following COVID‐19 vaccination based on cardiac MRI findings from 11 case series 4 .…”
mentioning
confidence: 99%
“…There, the genetic material can become endocytosed and assimilated to express spike protein that will initiate a cascade of localised immunological events [32]. Furthermore, histological observations showed that the rare severe myocarditis observed following mRNA COVID-19 vaccines could be attributed to forming a haptenic link between circulating spike protein and macromolecules of cardiomyocytes membrane [33]. It is worth noting that the presence of free spike protein circulating in the plasma of vaccinated subjects with the mRNA-1273 COVID-19 vaccine has been confirmed recently [34].…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%